Electronic, optical and photocatalytic properties of three-layer perovskite Dion–Jacobson phase CsBa2M3O10 (M = Ta, Nb): a DFT study. Issue 108 (19th October 2015) - Zahedi, Ehsan; Hojamberdiev, Mirabbos; Bekheet, Maged F.
Abstract : This work discloses structural, electronic and optical properties of three-layer perovskite Dion–Jacobson phase CsBa2 M3 O10 (M = Ta, Nb) using the DFT method. These semiconductors are UV-light-responsive photocatalysts. Abstract : Structure, electronic and optical properties have been studied to consider the photocatalytic activity of the three-layer perovskite Dion–Jacobson phase CsBa2 M3 O10 (M = Ta, Nb) using the density functional theory (DFT) method with the plane-wave pseudo-potential in the frame of the GGA proposed by Perdew, Burke, and Ernzerhof (PBE). CsBa2 Ta3 O10 and CsBa2 Nb3 O10 are indirect band gap semiconductors with different types of M–O bonds, from pure covalent to pure ionic. According to the symmetry breaking of MO6 octahedra from the O h point group to centrosymmetric ( D 4h ) and non-centrosymmetric ( C 4v ) point groups, the generation of local internal fields, the promotion of electron–hole pairs separation in the very initial process of photo-oxidation and the improvement in photocatalytic activity are suggested. Site and angular projected densities of state for CsBa2 M3 O10 show that the valence and conduction bands are made mainly of O and M orbitals, therefore the presence of a dipole moment at the MO6 octahedra will play an important role in separating electrons and holes. According to the optical properties simulation, the origin of interband transitions for CsBa2 Ta3 O10 and CsBa2 Nb3 O10 are from O-p and M-d orbitals. CsBa2 Ta3 O10 and CsBa2 Nb3 O10 are UV-light-responsive photocatalysts with plasmon energies of 13.16 and 12.07 eV, respectively, which can possibly oxidize/decompose organic pollutants and generate hydrogen from water splitting.